2015
DOI: 10.7705/biomedica.v36i1.2617
|View full text |Cite
|
Sign up to set email alerts
|

Producción y evaluación del antígeno recombinante Tes-30 de Toxocara canis para el inmunodiagnóstico de toxocariasis

Abstract: : desarrollo de experimentos Jorge H. Botero: asesoría en el análisis estadístico Edwin B. Patiño: asesoría en la purificación de proteínas Juan F. Alzate: coordinación general del proyecto Todos los autores participaron en la escritura del manuscrito. Producción y evaluación del antígeno recombinante TES-30 deToxocara canis para el inmunodiagnóstico de toxocariasis Introducción. Toxocara canis es un nematodo patógeno de cánidos que accidentalmente puede ser transmitido a los humanos. A pesar de la importancia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 31 publications
0
15
0
3
Order By: Relevance
“…Investigations of Spanish and Italian patients allergic to Anisakis demonstrated that Ani s 1 is the immunodominant specific allergen, and the quantification of IgE specific to Ani s 1 is able to discriminate between asymptomatic and allergic patients [51,63]. Several authors have also demonstrated that some lectins, such as TES-32, are immunodominant components for diagnostic purposes [73,74]. Yamasaki and colleagues reported an increase in specificity when they used the recombinant antigen in comparison with larval crude extract.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of Spanish and Italian patients allergic to Anisakis demonstrated that Ani s 1 is the immunodominant specific allergen, and the quantification of IgE specific to Ani s 1 is able to discriminate between asymptomatic and allergic patients [51,63]. Several authors have also demonstrated that some lectins, such as TES-32, are immunodominant components for diagnostic purposes [73,74]. Yamasaki and colleagues reported an increase in specificity when they used the recombinant antigen in comparison with larval crude extract.…”
Section: Discussionmentioning
confidence: 99%
“…Group 1: 21 negative control serum samples from apparently healthy individuals who have no precedent of living with domestic canines and double-negative in serial stool sampling tests for microscopic parasite examination and negative reactivity in an in-house IgG TES-ELISA previously developed and reported by Olave and colleagues in a T. canis reactivity study [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Group 4: 47 serum samples were obtained from patients with suspected toxocariasis based on clinical symptoms and signs (45 patients with OLMS suspicion and 2 patients with OLMS/VLMS suspicion). From this group, 43 samples were confirmed as positive for reactivity using the in-house IgG TES-ELISA [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…El diagnóstico de la enfermedad se puede realizar con un examen patológico de los diversos órganos afectados, sin embargo, por ser un método invasivo no se recomienda su uso de forma rutinaria, debido a esto, existen otras pruebas diagnósticas como el examen de materia fecal, en donde se busca identificar los huevos mediante el microscopio. La prueba diagnóstica más utilizada en la actualidad es la de ELISA con antígenos de excreción-secreción (Noriega Céspedes, 2019; Olave et al, 2015;Vargas Morellano, 2015).…”
Section: Introductionunclassified